Prevalence of loneliness and associated factors among older adults at Yilmana Densa District, West Gojjam Zone Amhara region, Ethiopia - Menewab Birhane, Desta; Demessie, Negesu Gizaw; Azagew, Abere Woretaw; Abate, Hailemichael Kindie; Mekonnen, Chilot Kassa (Frontiers in Epidemiology, 2025)
BackgroundLoneliness is a growing public health issue, particularly among older adults, owing to various internal and external factors related to ageing. However; evidence regarding this segment of the Ethiopian population is scarce. Therefore, this study aimed to assess the prevalence of loneliness and its associated factors among older adults in Ethiopia.MethodsThis community-based cross-sectional study was conducted from April 20 to May 20, 2023. A multistage systematic sampling technique, using an interviewer-administered questionnaire, was used. Data were entered into Epi Data version 4.6.0.0 and exported to the Stata version 14 software for analysis. A binary logistic regression analysis was conducted. Variables with a p-value < 0.20 in the Bivariable analysis were entered into multivariable regression and variables with a p-value < 0.05, with a 95% confidence interval (CI) were considered statistically significant.ResultsA total of 840 older adults took part with a 99.2% response rate. The overall prevalence of loneliness among older adults was 48.69%, with 95% CI = 45.31–52.07%. Living alone (OR=2.59, 95% CI = 1.11–6.05), the presence of chronic illness (OR = 1.69, 95% CI = 1.12–2.54), sleep time greater than 9 h (OR = 1.56, 95% CI = 1.08–2.22), impairment (OR = 5.09, 95% CI = 3.17–8.19), and poor social support (OR = 4.38, 95% CI = 2.53–7.59) were positively, but family size <5 (OR = 0.62, 95% CI = 0.45–0.85) and good health status (OR = 0.43, 95% CI = 0.27–0.66) were negatively associated with loneliness among older adults.ConclusionsNearly half of the participants felt lonely. Hence, every concerned body should pay special attention to this sidelined segment of the population by creating better social support networks, providing a conducive living environment, and providing aid to impaired older adults.